Assessment of Interleukin-17 levels in patients with hepatitis C Viral Infection - Mohammed, Rafal M.; A. Hamid, Zainab (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The roll of IL-17 during chronic hepatitis C virus (HCV) infection is not well understood. Elevated levels of IL-17 may increase the risk of liver fibrosis development in chronic HCV infection. However, the exact mechanism of how IL-17 contributes to the progression of HCV infection remains.Objectives: This study aimed to examine the association between HCV infection and IL-17. This was done by measuring the serum levels of interleukins and the viral load of HCV in patients with HCV infections. Methodology: The study included fifty HCV patients who were receiving treatment at the Gastroenterology and Hepatology Teaching Hospital / Medical City Complex in Baghdad. The study was conducted between November 2022 and April 2023, and the study groups were matched with 50 controls based on age and sex. Seven milliliters of venous blood samples were taken from all participants to test for anti-HCV antibodies using an ELISA kit, quantitative measurement of HCV RNA by PCR, and estimation of serum levels of IL-17.Results: The range of HCV viral RNA titers among the patients was 165-55595000 copies/ml, and all of them tested positive for anti-HCV antibodies. On the other hand, the control group tested negative for the virus. The mean concentration of IL-17 in the patients’ group was 1458.03 (±165.7) pg/ml, while the control group had a mean of 628.04 (±163.0) pg/ml (P < 0.0001). The R-value for HCV viral load and IL-17 was 0.1388. It is worth noting that the mean serum IL-17 concentration was highest among the patients aged  ≥ 50 years old.  As for the HCV patients on treatment, their mean viral load was 406,3051.90 copies/ml, and their mean IL-17 concentration was 1444.56 pg/ml. The patients who did not receive treatment had a mean higher mean viral load of 765,525.94 copies/ml, and their mean IL-17 concentration was 1484.19 pg/ml.Conclusion: The concentration of IL-17 was found to be significantly higher in patients with Hepatitis C virus (HCV), and it showed a weak positive correlation with HCV viral load. Moreover, older patients with HCV had higher levels of IL-17 in their blood. However, the measurement of HCV viral load and IL-17 did not show any significant differences in their readings.